KEINDAHAN RETORIKA DAN STRUKTUR BAHASA SEBAGAI I'JAZ AL-QUR'AN: ANALISIS SURAH AL-RAHMAN - Abdul Mustolif; Muhammad Ali Mustofa Kamal (JURNAL ILMIAH NUSANTARA, 2025)
This study discusses the miracle of the Qur'an (i'jaz) from the perspective of the beauty of language, especially rhetoric and structure in Surah Al-Rahman. This Surah has a distinctive feature in the form of the repetition of the verse "Fabi ayyi ālā'i rabbikumā tukadhdhibān" which appears 31 times. This repetition is not just a style of language, but has an important function in conveying messages and creating a rhythm that touches the heart. With the approach of linguistic analysis and the science of balaghah (Arabic rhetoric), this study shows that the structure and choice of words in Surah Al-Rahman are very beautiful, orderly, and cannot be matched by human works. This strengthens the belief that the Qur'an is a miracle from Allah revealed to the Prophet Muhammad SAW. This study also highlights how the beauty of language in the Qur'an can be an effective medium of da'wah because it is able to touch the emotional and spiritual aspects of its readers.